Do you like me? Behavioral and physical features for socially and emotionally engaging interactive systems - Esposito, Anna; Amorese, Terry; Cuciniello, Marialucia; Esposito, Antonietta M.; Cordasco, Gennaro (Frontiers in Computer Science, 2023)
With the aim to give an overview of the most recent discoveries in the field of socially engaging interactive systems, the present paper discusses features affecting users' acceptance of virtual agents, robots, and chatbots. In addition, questionnaires exploited in several investigations to assess the acceptance of virtual agents, robots, and chatbots (voice only) are discussed and reported in the Supplementary material to make them available to the scientific community. These questionnaires were developed by the authors as a scientific contribution to the H2020 project EMPATHIC (http://www.empathic-project.eu/), Menhir (https://menhir-project.eu/), and the Italian-funded projects SIROBOTICS (https://www.exprivia.it/it-tile-6009-si-robotics/) and ANDROIDS (https://www.psicologia.unicampania.it/android-project) to guide the design and implementation of the promised assistive interactive dialog systems. They aimed to quantitatively evaluate Virtual Agents Acceptance (VAAQ), Robot Acceptance (RAQ), and Synthetic Virtual Agent Voice Acceptance (VAVAQ).